The Transformation of Traditional Values in Lawomaru Folklore in the Oral Traditions of Nias Ethnic in the Modern Era - Regita Amelia; Difa Hartati; Sabrina Pramesuary Dwi Nanda; Shiwi Sulistyani; Yulisin Nazra; Fitriani Lubis (Journal of English Language and Education, 2026)
The rapid development of globalization and digital technology has significantly altered the way traditional cultural values are transmitted and understood, creating challenges for the sustainability of oral traditions among younger generations. Therefore, research on the transformation of traditional values in folklore is essential to understand how local wisdom can remain relevant in contemporary society. This study aims to analyze the transformation of traditional values contained in the folklore Laowomaru within the oral tradition of the Nias ethnic community in the modern era, identify the factors influencing these transformations, and examine their implications for cultural literacy and value transmission. The research employed a qualitative approach using a literature study method. Data were collected from books, scientific journals, theses, dissertations, and digital documents related to folklore, oral traditions, cultural values, and cultural transformation. The findings reveal that Laowomaru embodies traditional values such as family harmony, simplicity, obedience to rules, moral causality, trust, loyalty, and the consequences of betrayal. In the modern era, these values have undergone transformations in their forms, functions, and modes of application due to globalization, technological advancement, and changing social perspectives. Nevertheless, the core values remain preserved and continue to be adapted to contemporary contexts. This study contributes to cultural studies and literacy research by demonstrating that folklore serves not only as a cultural heritage but also as an educational medium for strengthening cultural literacy, character formation, and the preservation of local wisdom in the digital age.